LANGUAGE OF NATIONAL CULTURE: TRADITIONAL CLOTHES OF THE KAZAKHS (Journal of Philosophy Culture and Political Science, 2018)
Today in the age of globalization each nation in the universe is trying to save their individual peculiarity. By then it became vital importance to save Kazakh language and mentality, cultural treasures like national clothes. Formation of country’s image in the age of globalization is based on two concepts. The first is a ‘global’ society which absorbed postindustrial social values, and the second is in the meaning of ‘national’, which evokes national cultural values which go to deep corners of the history. To this point main concern of this article is connected with Kazakh national traditional clothes. There were made attempts to reveal correlation of traditional and modern fashion world and competence ability traditional Kazakh clothing with Western fashion world with its ancient Turkic symbolic meanings in the XXIst century.The study was conducted at the junction of language, ethnography, cultural anthropology. The methodical and methodological basis of the study was the work of leading Kazakh, Russian and foreign scientists.The authors of the article believe that, despite the processes of assimilation, globalization and modernization affecting all aspects of human culture, the language of the Kazakh national culture must be preserved and passed on to future generations.Key words: national cultural values, ethnicity, traditional clothes, modernity, language of culture.